Analysis Of The Influence Of Motivation On Tourists’ Visiting Decisions To The Mangrove Ketapang Urban Aquaculture Mauk, Tangerang Regency - Chintana Angelita Dewi; Feronika Berutu (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
This research was prompted by a decline in tourist visits to the Ketapang Mauk mangrove ecotourism area between May and September 2024, suggesting potential issues related to tourists’ motivation in making visitation decisions. The aim of this study is to determine whether motivation has an influence on tourists’ decisions to visit the area. A quantitative descriptive approach was employed, and data were collected through questionnaires distributed to 100 respondents. The data were analyzed using a simple linear regression method to examine the relationship between motivation and visiting decisions. The analysis also included supporting tests to measure the strength and direction of the influence. The results of the study indicate that motivation has a significant and positive influence on tourists’ decisions to visit Ketapang Mauk mangrove ecotourism. This finding highlights that motivational factors play a vital role in shaping tourists’ behavior. Based on this, it is recommended that tourism managers improve strategies that enhance visitor motivation. These may include improving tourism infrastructure and services, enhancing promotional activities, and offering unique, environmentally based educational experiences that align with tourists’ interests and values. Motivation should remain a key consideration in sustainable tourism planning for this destination.